Imigrantes Poloneses em Curitiba (PR): histórico, influência no desenvolvimento da cidade e reconhecimento de antepassados nos endereços - Rafaela Mascarenhas Rocha (Confins)
The pioneers polish immigrants arrived in Curitiba after leaving the state of Santa Catarina, by the hand of Sebastião Saporski, since 1871. This immigration is motivated by some Paraná’s authorities, with the intention of, as soon as they were living in the rural colonies on the outskirts of the city, the immigrants produced vegetables and create small animals, to serve the city market. Larger part of the polish immigrants in Curitiba are originally from the farm, however, it is not null the presence of Polish-Brazilians that worked in others productive sectors, including in local intellectuality and policy. In this paper we are going to bring part of the history of this immigrant group, a presentation about the process of integration that they had in Curitiba’s urban life along the 20th Century, as the creation of newspapers, cultural centers and sporting clubs in the first part of the century, and also look at the work of councilors Polish-Brazilians, that could see in the naming addresses process, an opportunity to honor their ancestors. For a better view about the following subject, we present maps with the location and the description of the streets, saying their dimensions, the commerce establishments, public transportation lines and other elements. E to finish, we present some people behind the streets, Polish-Brazilian will have their biographies presented here, in order to serve as an analysis about esteem, recognizing and prestige that they have – even posthumously – with the community.